Estimation Potential Areas of Skipjack Fishing (Katsuwonus pelamis) Based on Oceanographic Parameters in Makassar Strait - Wangi, Debby Aranindy Putri; Sunardi, Mr; Rahman, Muhammad Arif (JFMR (Journal of Fisheries and Marine Research), 2019)
Determination of regional fisheries based upon the experience of fishing master is one obstacle, because the spread of the fish moving in accordance with the fish habitat, while the fish habitat affected by the condition oceanographic parameters. Therefore, knowing the spread of fish based on oceanographic parameter is one of the indicators in determining potential areas of catching skipjack. Research method using descriptive observatif. The distribution results showed Sea Surface Temperature (SST) with average range between 28.45 °C – 30.93 °C, chlorophyll-a concentration between 0.28 mg/m3 – 0.62 mg/m3, and the speed of current between 0.01 m/s – 0.23 m/s. Correlation between SST, chlorophyll-a, and current towards the skipjack catches no significant relationship and their relationship is very low. Zone of fishing potential based on skipjack habitat obtained is 63 miles of fishing base shaped polygon area there are extents of 63,471,960.455 m2 withsamples coordinates of 00°3'00.0'' N and 119°19'48.0’’ E and 254,606,779.883 m2 with sample coordinates 00°21’21.5'' N and 119°46'12.0'' E.